Financial Liberalisation And Its Impact On The Efficiency, Productivity And Loan Quality Of Commercial Bank In Malaysia - Wong, Yoke Maan (2008)
This paper is to study the impact of the financial liberalisation measures exercised and its impacts on the efficiency, productivity and loan quality of commercial banks in Malaysia.